Savings Defaults and Payment Delays for Cash Transfers : Field Experimental Evidence from Malawi - Brune, Lasse; Gine, Xavier; Goldberg, Jessica; Yang, Dean (Washington, DC, 2016)
Financial products and transfer schemes are often designed to help individuals improve welfare by following through on intertemporal plans. This paper implements an artefactual field experiment in Malawi to test the ability of households to manage a cash windfall. This study varies whether 474 households receive a payment in cash or through direct deposit into pre-established accounts at a local bank. Payments are made immediately, with one day delay, or with eight days delay. Defaulting the payments into savings accounts leads to higher bank account balances, an effect that persists for several weeks. However, neither savings defaults nor payment delays affect the amount or composition of spending, suggesting that households manage cash effectively without the use of formal financial products.